Injecting Poultry Litter into Orchardgrass Hay. Issue 11 (16th June 2016) - Kulesza, Stephanie B.; Maguire, Rory O.; Thomason, Wade E.; Pote, Dan H.
ABSTRACT: Traditional surface application of poultry litter leaves nutrients vulnerable to loss through volatilization and runoff. However, injection can increase capture of these nutrients in agricultural fields. Therefore, a field experiment was conducted to determine the effects of poultry litter injection on orchardgrass ( Dactylis glomerata L.) hay yield and quality. Poultry litter was injected or surface applied using the Subsurfer poultry litter injector at the recommended agronomic rate (high) and half that rate (low) in 2012 and 2013 in an established field of orchardgrass. Soil was sampled to 15 cm and analyzed for soil nitrate. No significant differences in soil nitrate were detected between treatments. Although not always statistically significant, first cutting orchardgrass yields tended to be greater with surface litter application. Injected treatments had greater protein concentrations than their respective surface treatment, showing greater nitrogen uptake, when protein was weighted by yield. Protein was the same for high surface and low injected treatments showing that similar nitrogen (N) uptake was achieved.